EVALUASI DALAM PEMBELAJARAN BAHASA ARAB DI STAIN PAMEKASAN - Maimun — (Research Institute and Community Engagement of IAIN MADURA, 2011)
Evaluating study of arab Ianguage in STAIN Pamekasan represents one of the among study activity chain starts from study planning process, study execution and last is study evaluation. Evaluate at ability target (maharah) language which must be evaluated, and also at elements (‘anashir) language. As have been tolerated, that in arab Ianguage study at least there are four abilities (maharah) which must be mastered by educative participant to get predicate that he is one who have ability in the arab Ianguage field. The Maharah is Maharah Istima'(ability to correct reading), maharah al-Kalam (ability to converse), maharah Kitabah (ability to write), and maharah al-Qiraah (ability to read). Methodologically, study evaluation process of arab Ianguage in STAIN Pamekasan researched by using the qualitative approach with research type of case which its target is all currator lecturers of Arab Ianguage subject. Research result is obtained as follows: a) Step of assessment starting from preparation, execution, data-processing and follow-up, b) evaluation form intended here is some instruments used by all lecturer to get information about college student efficacy, in STAIN Pamekasan the pattern mentioned becomes two, that is tes form and non tes form, c) all lecturers more tend to using one approach of Ianguage tes, that is integrative approach